Aptamer and molecularly imprinted polymer: Synergistic recognition and sensing of dopamine. (20th January 2021) - Shen, Mingmei; Kan, Xianwen
Highlights: An aptamer-MIP based electrochemical sensor was developed for DA detection. Aptamer and MIP endowed the sensor with good selectivity to DA. AuNPs and rGO enabled the sensor to detect DA with high sensitivity. Fe(CN)6 3-/4- was replaced by DA current to overcome the uncertain specificity. Abstract: Specifically sensitive determination of dopamine (DA) from complex real samples is very important since DA plays a major role in the function of central nervous, which presents the necessary to develop an effective sensor for the assay of DA. In this work, a dual recognition strategy was developed through introducing DA-aptamer and molecularly imprinted polymer (MIP) on gold nanoparticles (AuNPs) and reduced graphene oxide (rGO) modified electrode. The selectivity and sensitivity of the prepared sensor were investigated upon the current response of DA itself to better represent the performances of the sensor. Compared with the single recognition element (MIP or aptamer) based sensors, the prepared dual recognition sensor displayed the highest selectivity to DA, which facilitated the proposed sensor for the detection of DA in real samples. Owing to the high surface and good conductivity of the modified AuNPs and rGO, the sensor showed a wide linear range and a low limit of detection of 5.0 × 10 -8 – 1.0 × 10 -5 mol/L and 4.7 × 10 -8 mol/L for the detection of DA, respectively. The proposed strategy of aptamer and MIP based sensor for electro-active target assay may be used as a general way for the development of other dual recognition based sensors. Graphical abstract: An aptamer-MIP based electrochemical sensor was developed for the detection of DA. Double recognition elements (aptamer and MIP) endowed the sensor with good selectivity to DA. The modified AuNPs and rGO enabled the sensor to sensitively detect DA. The dual recognition based sensor would broaden the scope of application of aptamer-MIP based sensor for template molecule sensitive and selective determination. Image, graphical abstract